Literature and religion in the German-speaking world from 1200 to the present day - Cooper, Ian 1979-; Walker, John 1956- (Cambridge University Press, 2019)
The relationship between literature and religion in German is unique in the European tradition. It is essential to the definition of German, Austrian and Swiss cultural identity in both the Protestant and Catholic traditions, and is crucial to our understanding of what has been called the 'special path' of German intellectual life. Offering in-depth essays by leading scholars, Literature and Religion in the German-Speaking World analyses this relationship from the beginnings of vernacular literature in German, via the Reformation, early-modern and Enlightenment periods, to the present day. It shows how such fundamental concepts as 'subjectivity', 'identity' and 'modernity' itself arise from the interrelation between religious and secular modes of understanding, and how this interrelation is inseparable from its expression in literature
Title from publisher's bibliographic system (viewed on 17 Sep 2019)
Introduction : literature and religion in the German-speaking world 1200 to the present / Ian Cooper and John Walker -- Pagan, Christian, secular : German writing until 1450 / Almut Suerbaum -- Literature and religion in the Holy Roman Empire 1450-1700 / Helen Watanabe-O'Kelly -- German literature and religion 1700-1770 : the shock and normalization of the infinite / John H. Smith -- Literature and religion in Germany 1770-1830 / Ian Cooper -- Culture, society and secularization : literature and religion in the German-speaking world 1830-1900 / John Walker -- Religion in German modernism 1900-1945 / Carolin Duttlinger -- German literature and religion 1945 to the present day / Daniel Weidner
Keywords: Geschichte 1200-2019; Religion and literature / Europe, German-speaking / History; German literature / History and criticism; Literatur; Religion -- Motiv; Deutsch